Improving Speaking Skills through the Role-Playing Method in Indonesian Language Learning - Rahmatia Karim, Andi (Universitas Pahlawan Tuanku Tambusai, 2025)
Speaking skills are an essential competency in Indonesian language learning that often face obstacles, such as low student confidence and a lack of meaningful practice opportunities. This study aims to improve students' speaking skills through the implementation of the Role-Playing Method. This research uses a Classroom Action Research (CAR) approach, conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were students of [State Class] at [School Name]. Data were collected through observation, speaking performance tests, interviews, and documentation, then analyzed descriptively both qualitatively and quantitatively. The results showed significant improvement in each cycle. The average score for speaking skills increased from the pre-cycle (62), to Cycle I (70), and reached 82 in Cycle II. Classical learning completeness also increased from 45% (pre-cycle), to 65% (Cycle I), and 90% (Cycle II). Qualitatively, students became more confident, active, and able to communicate in authentic simulation contexts. The conclusion of this research proves that the Role-Playing Method is effective in improving students' speaking skills, as it can create contextual learning situations, reduce anxiety, and train linguistic and pragmatic competencies in an integrated manner. Therefore, this method is recommended as an alternative innovative learning strategy for the Indonesian language subject.